Towards a Mobile-Mediated Action Learning Framework for Pre-Service Teachers: A Design-Based Research Perspective - Ndeunyema, Alpha Taapopi Mweuhanga (School of Education, 2024)
Although mobile devices are ubiquitous, their adoption as tools for teaching and learning in a 21st -century classroom remains a challenge. Mobile devices over the last decade have created significant shifts in society, changing how we communicate, access information and collaborate. However, in education, the pedagogical uses of mobile devices have been limited. This study argues that exposing pre-service teachers to mobile learning innovative pedagogies and technological enhancements can increase pedagogical uses of mobile devices. Thus, an intervention was designed, implemented and evaluated with pre-service teachers over four years with three different cohorts at the International University of Management (IUM) in Namibia. A design-based research (DBR) approach was utilised to draft design principles.The draft design principles guided the design of a Mobile-Mediated Learning Intervention (MMLI). Data were collected through a fact-finding study, pre-service teachers, created artefacts, observations, reflections, transcripts posted on a Padlet (a technological application), the formative evaluations of each iteration, as well as the Progress Report Journals (PRJ). As a key outcome of the DBR, a set of refined design principles for mobile-mediated learning experiences emerged. These principles have the potential to guide other educators in designing and facilitating pre-service mobile-mediated learning in authentic education contexts. Gadamer's Hermeneutic Learning Experience (HLE) theory was employed to understand the dialogical approach between the past (part) and the present (whole), pre-service teachers' perceptions of mobile learning (past) and experiences of using a mobile tool (present). Key findings demonstrated that mobilemediated learning experiences can be achieved through the construction of an authentic learning instructional approach which allows pre-service teachers to discuss, explore and collaborate to construct new knowledge and create new artefacts in realworld settings and tasks environment. The practical contribution of this research lies in the creation of design principles for a M-MLI for pre-service teachers. While the theoretical contribution of this study is the mobile-mediated action learning framework (M-MALF), which operationalizes mobile learning within pre-service teachers' programs in the Namibian context.